PERANCANGAN APLIKASI TOUR GUIDE PARIWISATA DI KOTA PADANG BERBASIS ANDROID - Ganda Yoga Swara; Hendri Zalmi (ITP Press, 2017)
Applications Tour Guide Tourism Padang city is an application designed to meet the needs of travelers. This app informs about travel, food and lodging in the city field and displays the route to the site in this application also uses the voice as an explanation for such travel. The system is designed in this study is an android-based application to determine the location of travel and the route to that location. In the design, the application uses the MySQL database and the application is using the Google Maps API to display a map. With this application the ability to use the Google Maps API has a guide that can help travel search for the shortest route to the tourist in the city of Padang. And in this application also uses the method Travelling salesman problem.